The Mill: A Worker's Memoir from 1945 to 1948 - Edwards, Alfred; Heron, Craig (Labour / Le Travail, 1999)
Historian Craig Heron introduces the 1945-48 memoir of Alfred Edwards, who worked at National Knitting MIlls, a textile mill in Hamilton, Ontario. Edwards, who had been a union activist prior to WWII, describes the changes in the relations of production that he observed upon his return to the plant from military service. He also discusses the decision of the shop union to join the Textile Workers Union of America, the struggle for local control in a bureaucratized international union, and the conflict between social democratic and communist unions at the Canadian Congress of Labour convention in Toronto in 1947.